Bioproduction of Quercetin and Rutinose Catalyzed by Rutinosidase: Novel Concept of "Solid State Biocatalysis" - Kapešová, Jana; Petrásková, Lucie; Markošová, Kristína; Rebroš, Martin; Kotik, Michael; Bojarová, Pavla; Křen, Vladimír (International journal of molecular sciences, 2019)
Quercetin is a flavonoid largely employed as a phytochemical remedy and a food or dietary supplement. We present here a novel biocatalytic methodology for the preparation of quercetin from plant-derived rutin, with both substrate and product being in mostly an undissolved state during biotransformation. This "solid-state" enzymatic conversion uses a crude enzyme preparation of recombinant rutinosidase from Aspergillus niger yielding quercetin, which precipitates from virtually insoluble rutin. The process is easily scalable and exhibits an extremely high space-time yield. The procedure has been shown to be robust and was successfully tested with rutin concentrations of up to 300 g/L (ca 0.5 M) at various scales. Using this procedure, pure quercetin is easily obtained by mere filtration of the reaction mixture, followed by washing and drying of the filter cake. Neither co-solvents nor toxic chemicals are used, thus the process can be considered environmentally friendly and the product of "bio-quality." Moreover, rare disaccharide rutinose is obtained from the filtrate at a preparatory scale as a valuable side product. These results demonstrate for the first time the efficiency of the "Solid-State-Catalysis" concept, which is applicable virtually for any biotransformation involving substrates and products of low water solubility.
Keywords: Glycoside Hydrolases; quercetin; Fungal Proteins; Rutin; Pichia; průmyslová mikrobiologie; rutin; Biocatalysis; Quercetin; fungální proteiny; biokatalýza; rutinosidase; Industrial Microbiology; disacharidy; “solid-state biocatalysis”; glykosidhydrolasy; Disaccharides; rutinose; Aspergillus niger